TGFβ drives NK cell metabolic dysfunction in human metastatic breast cancer. Issue 2 (10th February 2021) - Slattery, Karen; Woods, Elena; Zaiatz-Bittencourt, Vanessa; Marks, Sam; Chew, Sonya; Conroy, Michael; Goggin, Caitriona; MacEochagain, Colm; Kennedy, John; Lucas, Sophie; Finlay, David K; Gardiner, Clair M
Abstract : Background: Natural killer (NK) cells provide important immune protection from cancer and are a key requirement for particular immunotherapies. There is accumulating evidence that NK cells become dysfunctional during cancer. Overcoming NK cell exhaustion would be an important step to allow them to function optimally in a range of NK cell therapies, including those that depend on autologos circulating NK cells. We have previously demonstrated that NK cells undergo a normal metabolic reprogramming in response to cytokine activation and that this is required for optimal function. The objective of this work was to investigate if cellular metabolism of circulating NK cells is dysregulated in patients with metastatic breast cancer and if so, to gain insights into potential mechanisms underpinning this. Such discoveries would provide important insights into how to unleash the full activity of NK cells for maximum immunotherapy output. Methods: Single-cell analysis, metabolic flux and confocal analysis of NK cells from patients with metastatic breast cancer and healthy controls Results: In addition to reduced interferon-γ production and cytotoxicity, peripheral blood NK cells from patients had clear metabolic deficits including reduced glycolysis and oxidative phosphorylation. There were also distinct morphologically alterations in the mitochondria with increased mitochondrial fragmentation observed. Transforminggrowth factor-β (TGFβ) was identified as a key driver of this phenotype as blocking its activity reversed many metabolic and functional readouts. Expression of glycoprotein-A repetitions predominant (GARP) and latency associated peptide (LAP), which are involved with a novel TGFβ processing pathway, was increased on NK cells from some patients. Blocking the GARP–TGFβ axis recapitulated the effects of TGFβ neutralization, highlighting GARP as a novel NK cell immunotherapy target for the first time. Conclusions: TGFβ contributes to metabolic dysfunction of circulating NK cells in patients with metastatic breast cancer. Blocking TGFβ and/or GARP can restore NK cell metabolism and function and is an important target for improving NK cell-based immunotherapies.